Community Vibrancy and its Relationship with Safety in Philadelphia - Jensen, Shane T. (2020)
To what extent can the strength of a local urban community impact neighborhood safety? We constructed measures of community vibrancy based on a unique dataset of block party permit approvals from the City of Philadelphia. We use both regression modeling and propensity score matching to control for the economic, demographic and land use characteristics of the surrounding neighborhood when examining the relationship betweeen crime and our measures of community vibrancy. We conduct our analysis on aggregate levels of crime and community vibrancy from 2006 to 2015 as well as the trends in community vibrancy and crime over this time period. We find that neighborhoods with a higher number of block parties have a significantly higher crime rate, while those holding a greater proportion of spontaneous block party events have a significantly lower crime rate. We also find that neighborhoods with an increase in the ratio spontaneous block parties over time are significantly more likely to have a decreasing trend in total crime incidence over that same time period